Design of Data Visualization for Publication of Scientific Work by Lecturers of The Management Master's Program - Baskoro Baskoro; Fely Dany Prasetya; Iwan Tri Bowo; Prilian Ayu Winarni; M S Hasibuan (Proceeding International Conference on Information Technology and Business, 2021)
Research which is one of the elements of Tri Dharma has been carried out by lecturers as tasks and responsibilities that are carried out regularly every year. Create data visualizations using Google Data Studio, which can provide information on scientific publications for Master of Management lecturers based on the track record of submission of each lecturer based on the citation index of publishedscientific works, and find out the location or city of Master of Management lecturers from Bachelor to Doctoral. This research has succeeded in displaying data visualization of lecturers' scientific publications using Google Data Studio according to the citation index so as to help leaders evaluate lecturer's performance. The data sources used in this data visualization system with Google Data Studio are stored inGoogle Sheets. Data is collected from Google Scholar, Scopus, and WOS sites. This study also presents data on the history of lecturers' education by showing where the management master's lecturers have studied Keywords—Dashboard, Scientific Work Lecturers, Google Data Studio